Tugas dan Fungsi Manajemen Pendidik dan Tenaga Kependidikan - Lorensius Amon; Theresia Ping; Soerjo Adi Poernomo (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2021)
This paper intends to describe the duties and functions of educators and education management which are one part of the eight national education standards. This study uses a qualitative research method of literature study (library research). The results of this study indicate that the duties and management functions of educators and education personnel are carried out based on statutory regulations with the aim of improving the quality of national education, developing science, technology and arts, as well as serving the community. The implementation of duties and functions of educators and education management consists of six components, namely: (a) planning, (b) recruitment, (c) job placement, (d) compensation, (e) coaching and development, (f) evaluating. Management functions and duties have implications for schools in dealing with shortages of educators and education personnel through recruitment. Coaching and development is also carried out through individual learning, training and advanced education, both by working groups of teachers, schools, and the education office.